2015
DOI: 10.1016/j.jiph.2015.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and preventive behaviors related to dengue vector breeding control measures among adults in communities of Vientiane, capital of the Lao PDR

Abstract: This research aimed to determine the knowledge, attitudes and preventive behaviors (KAP) of adults in relation to dengue vector control measures in the communities of Vientiane, the capital of the Lao PDR. A total of 207 respondents were actively participating in this cross-sectional descriptive study in 2011. Representatives of households were interviewed face-to-face by six trained interviewers using a structured questionnaire. KAP reliabilities of 0.89, 0.91 and 0.95 were reported in the pilot sample of 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 16 publications
4
42
0
7
Order By: Relevance
“…Dengue-related KAPs have been shown to be associated with the following demographic variables: sex, age, marital status, education, literacy, employment, occupation, income, ethnicity, and religion [26–37]. Other risk factors include frequent fogging of the neighborhood [38], adequate resources and assistance from public health staff [27], community support or governmental infrastructure to control neighboring and public spaces [39], and having a reputable source of information such as health personnel or head of the village [40]. In Ecuador, dengue risk was found to be associated with older female heads of household, access to piped water in the home, poor housing condition, household water storage, higher housing density, lack of knowledge, and low risk perception [41,42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dengue-related KAPs have been shown to be associated with the following demographic variables: sex, age, marital status, education, literacy, employment, occupation, income, ethnicity, and religion [26–37]. Other risk factors include frequent fogging of the neighborhood [38], adequate resources and assistance from public health staff [27], community support or governmental infrastructure to control neighboring and public spaces [39], and having a reputable source of information such as health personnel or head of the village [40]. In Ecuador, dengue risk was found to be associated with older female heads of household, access to piped water in the home, poor housing condition, household water storage, higher housing density, lack of knowledge, and low risk perception [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Demographic variables that have been reported to be associated with KAPs in one or more study include sex, age, marital status, education, literacy, employment, occupation, income, ethnicity, and religion (17,21,22,24,26,28,30–35). Other social-ecological factors associated with KAPs include frequent fogging of the neighborhood (20), adequate resources and assistance from public health staff (21), presence of dengue in the neighborhood (36,37), presence of mosquitoes in the neighborhood (35), internet access (30), community support or governmental infrastructure to control neighboring and public spaces (38), and having a reputable source of information such as health personnel or head of the village (27).…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaires used in the studies differed greatly from each other. Thus, in some studies, the dengue knowledge component of the questionnaire included questions on disease transmission and dengue signs and symptoms 14 while others focused exclusively on mosquito biting and breeding habits 18,19 . Several studies reported that they applied convenience sampling 11,16,20 , and some studies did not specify a sampling method 12,14 , which might have compromised the generalizability of the findings.…”
Section: Introductionmentioning
confidence: 99%
“…This finding was similar with the findings in a study in Vientiane. 25 Association between socio-demographic and KAP regarding dengue fever was analysed by using Pearson's Chi Square test. High education level was significantly associated with good practice of prevention towards dengue infection.…”
Section: Discussionmentioning
confidence: 99%